Undergraduate students' perception of artificial intelligence for enhancing educational practices: Opportunities, challenges, and ethical considerations - Chidinma, Abe Ezinne; Yinka, Kasumu Rebecca (Global Journal of Social Sciences Studies, 2025)
This study employed a descriptive survey design to examine undergraduate students' perceptions of artificial intelligence (AI) in enhancing educational practices, focusing on opportunities, challenges, and ethical considerations. Conducted in the Faculty of Education at the University of Port Harcourt, the study targeted a population of 160 students, 98 from the Department of Curriculum Studies and Educational Technology and 62 from the Department of Educational Management. A sample of 80 students was selected using a stratified sampling technique. Data were collected using a structured questionnaire titled "Undergraduate Students' Perception of Artificial Intelligence for Enhancing Educational Practices: Opportunities, Challenges, and Ethical Considerations" (USPAIEEPOCEC), consisting of 20 items. The instrument's validity was established through face and content validation, and its reliability was confirmed using Cronbach’s Alpha, yielding a coefficient of 0.74. Mean scores were used to answer research questions, while the Z-test was applied to analyze the hypotheses. Findings revealed that AI enhances accessibility and diversity in education by providing assistive technologies such as speech recognition and text-to-speech tools. The study recommended that higher education institutions incorporate AI literacy programs into their curricula to equip students and educators with the knowledge and skills to understand AI applications and ethical implications; developers must emphasize transparency in the decision-making processes of AI.